Question
upstudy study bank question image url

The deriations from the mean of a set of numbers are \( (k-13)^{2},(k+7) \); \( -2, k \) and \( (k+2)^{2} \), Where \( k \) is a constant. Find the value of \( k \) if the mean deviation

Ask by Goodwin Stanley. in Ghana
Feb 14,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( k = 5 \)

Solution

To find the value of \( k \) given the deviations from the mean, we need to set up the equation for the mean deviation. The mean deviation is the average of the absolute deviations from the mean. The deviations from the mean are given as: 1. \( (k-13)^{2} \) 2. \( (k+7) \) 3. \( -2 \) 4. \( k \) 5. \( (k+2)^{2} \) Let's denote the deviations as \( d_1, d_2, d_3, d_4, d_5 \): - \( d_1 = (k-13)^{2} \) - \( d_2 = (k+7) \) - \( d_3 = -2 \) - \( d_4 = k \) - \( d_5 = (k+2)^{2} \) The mean deviation \( M \) can be calculated as: \[ M = \frac{1}{n} \sum_{i=1}^{n} |d_i| \] where \( n \) is the number of deviations. In this case, \( n = 5 \). Therefore, we need to calculate: \[ M = \frac{1}{5} \left( |(k-13)^{2}| + |(k+7)| + |-2| + |k| + |(k+2)^{2}| \right) \] Since all terms are non-negative, we can drop the absolute value signs: \[ M = \frac{1}{5} \left( (k-13)^{2} + (k+7) + 2 + k + (k+2)^{2} \right) \] Now, let's simplify this expression step by step. 1. Calculate \( (k-13)^{2} \): \[ (k-13)^{2} = k^{2} - 26k + 169 \] 2. Calculate \( (k+2)^{2} \): \[ (k+2)^{2} = k^{2} + 4k + 4 \] 3. Combine all terms: \[ M = \frac{1}{5} \left( (k^{2} - 26k + 169) + (k + 7) + 2 + k + (k^{2} + 4k + 4) \right) \] Combine like terms: \[ = \frac{1}{5} \left( 2k^{2} - 20k + 182 \right) \] Now, we can set the mean deviation \( M \) equal to a specific value if provided, or we can solve for \( k \) if we have additional conditions. However, since the problem does not specify a value for the mean deviation, we will need to find \( k \) such that the mean deviation is minimized or equals zero. Let's assume we want to find \( k \) such that the mean deviation is minimized. We can set the derivative of \( M \) with respect to \( k \) to zero and solve for \( k \). Let's calculate the derivative of \( M \) and set it to zero. The expression for \( M \) is: \[ M = \frac{1}{5} \left( 2k^{2} - 20k + 182 \right) \] Taking the derivative: \[ \frac{dM}{dk} = \frac{1}{5} (4k - 20) \] Setting the derivative to zero: \[ 4k - 20 = 0 \] Solving for \( k \): \[ 4k = 20 \implies k = 5 \] Now, let's confirm that this value of \( k \) is indeed a minimum by checking the second derivative: \[ \frac{d^2M}{dk^2} = \frac{1}{5} \cdot 4 = \frac{4}{5} > 0 \] Since the second derivative is positive, \( k = 5 \) is a minimum. Thus, the value of \( k \) is: \[ \boxed{5} \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To solve for \( k \), we first need to take the mean deviation formula into account, which is defined as the average of the absolute deviations from the mean. The given deviations from the mean are: 1. \( (k-13)^2 \) 2. \( (k+7) \) 3. \( -2 \) 4. \( k \) 5. \( (k+2)^2 \) To find \( k \), we set up the equation by summing the deviations and dividing by the number of terms, which is 5: \[ \text{Mean Deviation} = \frac{(k-13)^2 + (k+7) + (-2) + k + (k+2)^2}{5} \] Since we need the mean deviation to be equal to zero for the mean itself to lie at the center (given that some deviations are negative), we can equate the sum of deviations to zero and solve for \( k \). Let's sum everything: \[ (k-13)^2 + (k+7) - 2 + k + (k+2)^2 = 0 \] Expanding and combining like terms: 1. \( (k-13)^2 = k^2 - 26k + 169 \) 2. \( (k+2)^2 = k^2 + 4k + 4 \) Combining: \[ k^2 - 26k + 169 + k + 7 - 2 + k + k^2 + 4k + 4 = 0 \] \[ 2k^2 - 20k + 178 = 0 \] Now solve this quadratic equation using the quadratic formula: \[ k = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] Where \( a = 2 \), \( b = -20 \), and \( c = 178 \): \[ b^2 - 4ac = (-20)^2 - 4 \cdot 2 \cdot 178 = 400 - 1424 = -1024 \] Since the discriminant is negative, there are no real solutions for \( k \). Hence, we may review the derivation steps or conditions for any further assumptions or evaluations for potential complex outcomes. This mathematical scenario teaches us the value of checking our steps as much as we strive for resolution in deriving unknowns! Happy problem-solving!

Related Questions

Latest Statistics Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy